A preliminary investigation of the entomofauna composition of forensically important necrophagous insects in Al-Madinah Al-Munawwarah region, Kingdom of Saudi Arabia. Issue 1 (1st January 2020) - Al-Dakhil, Abeer Ali; Alharbi, Shorooq A.
ABSTRACT: The key role in forensic entomology is the study of entomofauna composition through species identification, succession, colonization, and developmental rate. In this study, rabbit carcasses were used as a model to identify the forensic insect species in Al-Madinah Al-Munawwarah, Saudi Arabia. The appearance and succession of these insects can help in the estimation of the minimum postmortem interval (mPMI) and in many other applications in this region. During the decomposition process, the most important forensic insects observed were from the orders Diptera and Coleoptera. Seven species in five families of Diptera and four families of Coleoptera were identified. The most abundant species in the area that colonized the carcasses were Chrysomya albiceps Widemann (Diptera: Calliphoridae) and Dermestes maculatus De Geer, which can be used for mPMI estimations. This study was the first conducted in Al-Madinah Region to provide a qualitative assessment of forensically important necrophagous species in this region.